Electrochemical Deposition: Thermoelectric Characterization Platform for Electrochemically Deposited Materials (Adv. Electron. Mater. 4/2020). (14th April 2020) - Barati, Vida; Garcia Fernandez, Javier; Geishendorf, Kevin; Schnatmann, Lauritz Ule; Lammel, Michaela; Kunzmann, Alexander; Pérez, Nicolás; Li, Guodong; Schierning, Gabi; Nielsch, Kornelius; Reith, Heiko
Abstract : Full thermoelectric characterization of electrochemically deposited films is investigated by Heiko Reith and co‐workers in article 1901288, using an in‐plan zT characterization platform as shown on the back‐cover image. The overlay of the cover represents the temperature distribution in the deposit. Micro thermoelectric leg pairs in the background demonstrate one application of electrodeposited materials.